Cyber nomenclaturalists and the “CESA itch” - O’hara, James E. (Zootaxa, 2011)
Not long ago, Neal Evenhuis (2008) treated us to a historical review of the mental affliction known by the quaint term “mihi itch”. This condition is unique to taxonomists and manifests itself in the sufferer’s near uncontrollable desire to name species. The mihi itch is less prevalent than it once was, but in recent years a new “itch” has afflicted some of our fellow taxonomists. This I term the “CESA itch” (see below), and you may have seen its effects already in a taxon of interest to you.